A mixed-methods systematic review of mental health activities among urban left-behind children in mainland China - Siyu Long; Siyu Long; Zainal Bin Madon; Noris Mohd Norowi; Mei Foong Ang (Frontiers in Public Health)
IntroductionThe mental health of left-behind children has garnered attention from Chinese scholars in recent years. Although several interventions have been implemented to address these children’s mental health in urban areas, a gap remains in understanding the types of interventions, their effectiveness, and the factors that act as barriers or facilitators during the implementation process.MethodsA mixed methods systematic review informed by JBI methodology. Researchers conducted a comprehensive search of databases in both English and Chinese, covering the years 2005 to 2023. The initial search took place in January 2024 and was updated in March 2024. This study includes all studies results available up to December 31, 2023. The protocol has been registered on PROSPERO (CRD42023384078) and includes 14 studies in the review.ResultsThe activity categories included group psychological activities, individual family activities and multiple formats services. Three barriers to implementation emerged: social workers, activities and parents. The facilitators were parents and activity design.ConclusionThis review revealed that some studies suffered from poor data collection methods and data quality. Studies on services for mental health in urban left-behind children requires methodologically robust study designs for broader dissemination and rigorous evaluation.Systematic review registrationPROSPERO, CRD42023384078, available from: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023384078.